Sulfide-based inorganic solid electrolyte material, solid electrolyte, solid electrolyte membrane and lithium-ion battery
By adjusting the particle size distribution of sulfide-based inorganic solid electrolyte materials, the problem of low lithium ion conductivity is solved, the balance between electrochemical stability and lithium ion conductivity is achieved, and the performance of lithium ion batteries is improved.
Patent Information
- Application Number
- CN202180028354.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-05
- Filing Date
- 2021-03-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-03-12
AI Technical Summary
The existing sulfide-based inorganic solid electrolyte materials have low lithium ion conductivity and cannot fully meet the needs of lithium-ion batteries.
By adjusting the particle size distribution of the sulfide-based inorganic solid electrolyte material, the ratio D90/Dm between the most frequency particle size Dm and the particle size D90 with a cumulative frequency of 90% is 1.6 or more and 8.0 or less, so as to improve the electrochemical stability and Lithium ion conductivity.
It achieves an excellent balance between electrochemical stability and lithium ion conductivity, and improves the performance of lithium ion batteries.
Smart Images

Figure CN115428099B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sulfide-based inorganic solid electrolyte material, a solid electrolyte, a solid electrolyte membrane and a lithium ion battery. Background Art
[0002] Generally, lithium-ion batteries are used as power sources for small portable devices such as mobile phones and notebook computers. In addition, recently, lithium-ion batteries have begun to be used as power sources for electric vehicles, power storage, and the like in addition to small portable devices.
[0003] At present, commercially available lithium-ion batteries use electrolytes containing flammable organic solvents. On the other hand, lithium-ion batteries that replace electrolytes with solid electrolytes and make the batteries all solid (hereinafter also referred to as all-solid-state lithium-ion batteries) do not use flammable organic solvents in the batteries, so it is believed that safety devices are simplified and manufacturing costs and productivity are excellent.
[0004] As a solid electrolyte material used for such a solid electrolyte, for example, a sulfide-based inorganic solid electrolyte material is known.
[0005] Patent document 1 (Japanese Patent Publication No. 2016-27545) describes a sulfide-based solid electrolyte material, characterized in that it has a peak at 2θ=29.86°±1.00° in X-ray diffraction measurement using CuKα rays, and has Li 2y+3 The composition of PS4 (0.1≤y≤0.175).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: Japanese Patent Application Publication No. 2016-27545. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, although sulfide-based inorganic solid electrolyte materials are excellent in electrochemical stability and lithium ion conductivity, their lithium ion conductivity is still much lower than that of electrolyte solutions and thus they are not sufficiently satisfactory as solid electrolyte materials.
[0011] In summary, sulfide-based inorganic solid electrolyte materials for lithium-ion batteries are required to have electrochemical stability and further improved lithium ion conductivity.
[0012] The present invention has been made in view of the above circumstances, and provides a sulfide-based inorganic solid electrolyte material having an excellent balance between electrochemical stability and lithium ion conductivity.
[0013] Means used to solve problems
[0014] The present inventors have conducted intensive research on the particle size distribution of sulfide-based inorganic solid electrolyte materials in order to provide a sulfide-based inorganic solid electrolyte material having an excellent balance between electrochemical stability and lithium ion conductivity. As a result, it was found that in the number-based particle size distribution obtained from the image observed by a scanning electron microscope (SEM), the most frequent particle size was defined as Dm [μm] and the particle size with a cumulative frequency of 90% was defined as D 90 [μm], D 90 The present invention has been completed based on the fact that a sulfide-based inorganic solid electrolyte material having a / Dm value of a specific value or more has an excellent balance between electrochemical stability and lithium ion conductivity.
[0015] That is, according to the present invention, there is provided a sulfide-based inorganic solid electrolyte material,
[0016] It is a sulfide-based inorganic solid electrolyte material with lithium ion conductivity.
[0017] The above-mentioned sulfide-based inorganic solid electrolyte material is in the form of particles.
[0018] In the number-based particle size distribution of the sulfide-based inorganic solid electrolyte material obtained from an image observed with a scanning electron microscope (SEM), the most frequent particle size is denoted as Dm [μm], and the particle size at which the cumulative frequency of the number-based particle size distribution is 90% is denoted as D 90 [μm], D 90 The / Dm value is 1.6 or more and 8.0 or less.
[0019] Furthermore, according to the present invention, there is provided a solid electrolyte comprising the above-mentioned sulfide-based inorganic solid electrolyte material.
[0020] Further, according to the present invention, there is provided a solid electrolyte membrane comprising the above-mentioned solid electrolyte as a main component.
[0021] Further, according to the present invention, a lithium ion battery is provided.
[0022] The lithium ion battery comprises a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer.
[0023] At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material.
[0024] Furthermore, according to the present invention, a method for producing a sulfide-based inorganic solid electrolyte material is provided.
[0025] The invention relates to a method for producing the above-mentioned sulfide-based inorganic solid electrolyte material, comprising:
[0026] Step (A), preparing a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and phosphorus sulfide;
[0027] Step (B) of mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material to chemically react lithium sulfide and phosphorus sulfide as raw materials and simultaneously vitrify them to obtain a sulfide-based inorganic solid electrolyte material in a glassy state; and
[0028] Step (C), by classifying the obtained sulfide-based inorganic solid electrolyte material, 90 The / Dm value is adjusted to be within the range of 1.6 to 8.0.
[0029] Effects of the Invention
[0030] According to the present invention, a sulfide-based inorganic solid electrolyte material having an excellent balance between electrochemical stability and lithium ion conductivity can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a cross-sectional view showing an example of the structure of a lithium ion battery according to an embodiment of the present invention.
[0032] Figure 2 This is a graph showing the number-based particle size distribution of the sulfide-based inorganic solid electrolyte materials obtained in Examples and Comparative Examples.
[0033] Figure 3 This is a graph showing the number-based particle size distribution of the sulfide-based inorganic solid electrolyte materials obtained in Example 5 and Example 6. DETAILED DESCRIPTION
[0034] The following is an explanation of the embodiments of the present invention using the accompanying drawings. It should be noted that in all the drawings, the same components are marked with common symbols, and the description is appropriately omitted. In addition, the drawings are schematic diagrams and are inconsistent with the actual size ratios. Unless otherwise specified, the numerical range "A to B" means above A and below B.
[0035] [Sulfide-based inorganic solid electrolyte materials]
[0036] First, the sulfide-based inorganic solid electrolyte material according to the present embodiment will be described.
[0037] The sulfide-based inorganic solid electrolyte material of the present embodiment is a sulfide-based inorganic solid electrolyte material having lithium ion conductivity. The sulfide-based inorganic solid electrolyte material is in the form of particles. In the number-based particle size distribution of the sulfide-based inorganic solid electrolyte material obtained from an observation image using a scanning electron microscope (SEM), the most frequent particle size is set to Dm [μm], and the particle size at which the cumulative frequency of the number-based particle size distribution is 90% is set to D 90 [μm], D 90 The / Dm value is 1.6 or more and 8.0 or less.
[0038] The sulfide-based inorganic solid electrolyte material of this embodiment is 90 When the / Dm value is within the above range, the lithium ion conductivity can be improved while maintaining the electrochemical stability well.
[0039] Although the reason is not clear, the following reasons can be inferred.
[0040] D 90 When the / Dm value is within the above range, the particle size distribution of the sulfide-based inorganic solid electrolyte material is wide, and small particles enter the gaps between large particles, thereby the particles become close, and as a result, the contact between particles is improved, and therefore, it is believed that the lithium ion conductivity is improved. Here, the particle size of the sulfide-based inorganic solid electrolyte material is usually measured by a laser diffraction scattering particle size distribution determination method. However, according to the research of the present inventors, if a laser diffraction scattering particle size distribution determination method is used, agglomerates of the sulfide-based inorganic solid electrolyte material will be generated during the measurement, and therefore, the particle size of the sulfide-based inorganic solid electrolyte material cannot be accurately measured.
[0041] That is, according to the research of the present inventors, it was found for the first time that the particle size of the sulfide-based inorganic solid electrolyte material can be accurately evaluated by obtaining the particle size of the sulfide-based inorganic solid electrolyte material from the observation image of the scanning electron microscope (SEM). As a result, it was found for the first time that by using D 90 When the value of / Dm is within the above range, the lithium ion conductivity can be improved.
[0042] Here, D 90 It refers to the particle size at which the cumulative value of the particle size distribution obtained by measuring the tangential diameter in a certain direction (Feret diameter) is 90%. In addition, the description of the particle size distribution refers to the value obtained by measuring the particle size of 3,000 or more particles randomly selected from the SEM image.
[0043] In the sulfide-based inorganic solid electrolyte material of this embodiment, D 90 / Dm is 1.6 or more and 8.0 or less. From the viewpoint of further improving lithium ion conductivity, D90 / Dm is preferably greater than 1.8, more preferably greater than 2.0, further preferably greater than 2.3, and particularly preferably greater than 2.5. Moreover, from the viewpoint of being able to further reduce the thickness of the obtained solid electrolyte membrane, it is preferably less than 5.0, more preferably less than 4.0, and further preferably less than 3.5.
[0044] In the sulfide-based inorganic solid electrolyte material of the present embodiment, the mode particle size Dm is preferably 10.0 μm or less, more preferably 8.0 μm or less, and even more preferably 6.0 μm or less, from the viewpoint of being able to further reduce the thickness of the obtained solid electrolyte membrane.
[0045] The lower limit of the mode particle size Dm is not particularly limited, but is, for example, 0.1 μm or more, and preferably 1.0 μm or more, from the viewpoint of handleability.
[0046] From the viewpoint of further improving electrochemical stability, stability in water or air, handleability, and the like, the sulfide-based inorganic solid electrolyte material of the present embodiment preferably contains Li, P, and S as constituent elements.
[0047] In addition, for the sulfide-based inorganic solid electrolyte material of the present embodiment, from the viewpoint of further improving lithium ion conductivity, electrochemical stability, stability in water or air, and handleability, the molar ratio Li / P of the Li content to the P content in the sulfide-based inorganic solid electrolyte material is preferably 1.0 or more and 5.0 or less, more preferably 2.0 or more and 4.0 or less, further preferably 2.5 or more and 3.8 or less, further preferably 2.8 or more and 3.6 or less, further preferably 3.0 or more and 3.5 or less, further preferably 3.1 or more and 3.4 or less, particularly preferably 3.1 or more and 3.3 or less, and the molar ratio S / P of the S content to the P content is preferably 2.0 or more and 6.0 or less, more preferably 3.0 or more and 5.0 or less, further preferably 3.5 or more and 4.5 or less, further preferably 3.8 or more and 4.2 or less, further preferably 3.9 or more and 4.1 or less, and particularly preferably 4.0.
[0048] Here, the contents of Li, P, and S in the sulfide-based inorganic solid electrolyte material of the present embodiment can be determined by, for example, ICP emission spectrometry analysis or X-ray analysis.
[0049] In the sulfide-based inorganic solid electrolyte material of the present embodiment, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is preferably 0.95×10-3 S cm -1 More preferably, 1.1×10 -3 S cm -1 More preferably, 1.3×10 -3 S cm -1 above.
[0050] When the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the present embodiment is equal to or higher than the above lower limit, a lithium ion battery with further excellent battery characteristics can be obtained. Furthermore, when such a sulfide-based inorganic solid electrolyte material is used, a lithium ion battery with further excellent input-output characteristics can be obtained.
[0051] The sulfide-based inorganic solid electrolyte material of the present embodiment has excellent electrochemical stability. Here, electrochemical stability refers to, for example, the property of being difficult to oxidize and reduce in a wide voltage range. More specifically, in the sulfide-based inorganic solid electrolyte material of the present embodiment, the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material measured under the conditions of a temperature of 25°C, a scanning voltage range of 0 to 5V, and a voltage scanning rate of 5mV / second is preferably 0.50μA or less, more preferably 0.20μA or less, further preferably 0.10μA or less, further preferably 0.05μA or less, and particularly preferably 0.03μA or less.
[0052] When the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material is equal to or less than the above upper limit, oxidative decomposition of the sulfide-based inorganic solid electrolyte material in the lithium ion battery can be suppressed, which is preferable.
[0053] The lower limit of the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material is not particularly limited, but is, for example, 0.0001 μA or more.
[0054] The sulfide-based inorganic solid electrolyte material of the present embodiment can be used for any purpose requiring lithium ion conductivity. Among them, the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably used for lithium ion batteries. More specifically, it is used for the positive electrode active material layer, the negative electrode active material layer, the electrolyte layer, etc. in the lithium ion battery. Furthermore, the sulfide-based inorganic solid electrolyte material of the present embodiment is suitable for constituting the positive electrode active material layer, the negative electrode active material layer, the solid electrolyte layer, etc. of an all-solid-state lithium ion battery, and is particularly suitable for constituting the solid electrolyte layer of an all-solid-state lithium ion battery.
[0055] An example of an all-solid-state lithium-ion battery to which the sulfide-based inorganic solid electrolyte material of the present embodiment is applied is a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are stacked in this order.
[0056] [Method for producing sulfide-based inorganic solid electrolyte material]
[0057] Next, a method for producing the sulfide-based inorganic solid electrolyte material according to the present embodiment will be described.
[0058] The sulfide-based inorganic solid electrolyte material of the present embodiment can be obtained, for example, by a production method including the following steps (A), (B) and (C). In addition, as required, the production method of the sulfide-based inorganic solid electrolyte material of the present embodiment may further include the following step (D). Step (D) may be performed before step (C) or after step (C).
[0059] Step (A): a step of preparing a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and phosphorus sulfide;
[0060] Step (B): a step of mechanically treating a raw material composition of a sulfide-based inorganic solid electrolyte material to chemically react lithium sulfide and phosphorus sulfide as raw materials and simultaneously vitrify the raw materials to obtain a glass-state sulfide-based inorganic solid electrolyte material;
[0061] Step (C): The obtained sulfide-based inorganic solid electrolyte material is subjected to a classification treatment to obtain D 90 A step of adjusting the / Dm value to a range of 1.6 to 8.0;
[0062] Step (D): a step of heating the obtained glassy sulfide-based inorganic solid electrolyte material to crystallize at least a portion of it.
[0063] (Step (A) of Preparing a Raw Inorganic Composition)
[0064] First, a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and phosphorus sulfide as raw materials at a specific ratio is prepared. Here, the mixing ratio of each raw material in the raw material composition is adjusted so that the obtained sulfide-based inorganic solid electrolyte material has a desired composition ratio.
[0065] The raw material composition of the sulfide-based inorganic solid electrolyte material may further contain lithium nitride.
[0066] The method for mixing the raw materials is not particularly limited as long as it is a mixing method that can uniformly mix the raw materials. For example, mixing can be performed using a ball mill, a bead mill, a vibration mill, a percussion pulverizer, a mixer (a pug mixer, a ribbon mixer, a drum mixer, a tumble mixer, a V-type mixer, etc.), a kneader, a twin-screw kneader, a jet mill, etc.
[0067] Mixing conditions such as stirring speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the mixture when mixing the raw materials can be appropriately determined according to the amount of the mixture to be treated.
[0068] The lithium sulfide used as a raw material is not particularly limited, and commercially available lithium sulfide can be used. For example, lithium sulfide obtained by reacting lithium hydroxide with hydrogen sulfide can also be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferred to use lithium sulfide with less impurities.
[0069] Here, in this embodiment, lithium sulfide also includes lithium polysulfide. As lithium sulfide, Li2S is preferred.
[0070] There are no particular limitations on the phosphorus sulfide used as a raw material, and commercially available phosphorus sulfide (e.g., P2S5, P4S3, P4S7, P4S5, etc.) can be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and from the viewpoint of suppressing side reactions, it is preferred to use phosphorus sulfide with fewer impurities. As the phosphorus sulfide, P2S5 is preferred. In addition, it is also possible to use elemental phosphorus (P) and elemental sulfur (S) in a comparable molar ratio instead of phosphorus sulfide. As long as elemental phosphorus (P) and elemental sulfur (S) are industrially produced and sold substances, they can be used without particular limitations.
[0071] As a raw material, lithium nitride can be used. Here, since nitrogen in lithium nitride is discharged into the system in the form of N2, the inorganic compound as a raw material can increase only the Li composition for the sulfide-based inorganic solid electrolyte material including Li, P and S as constituent elements by using lithium nitride.
[0072] The lithium nitride of this embodiment is not particularly limited, and commercially available lithium nitride (e.g., Li3N, etc.) can be used. For example, lithium nitride obtained by reacting metallic lithium (e.g., Li foil) with nitrogen can be used. From the perspective of obtaining a high-purity solid electrolyte material and suppressing side reactions, it is preferred to use lithium nitride with few impurities.
[0073] (Step (B) of Obtaining a Glassy Sulfide Inorganic Solid Electrolyte Material)
[0074] Next, the raw material composition of the sulfide-based inorganic solid electrolyte material is mechanically treated to chemically react and vitrify the raw materials of lithium sulfide, phosphorus sulfide, and, if necessary, lithium nitride, thereby obtaining a glassy sulfide-based inorganic solid electrolyte material.
[0075] Here, the mechanical treatment can vitrify two or more inorganic compounds by mechanically colliding them to chemically react with each other, and examples thereof include mechanochemical treatment, etc. Here, the mechanochemical treatment is a method of vitrifying the target composition while applying mechanical energy such as shear force or collision force.
[0076] In the step (B), the mechanochemical treatment is preferably a dry mechanochemical treatment from the viewpoint of easily achieving an environment in which moisture and oxygen are removed at a high level.
[0077] When mechanochemical treatment is used, each raw material can be mixed while being crushed into fine particles, thereby increasing the contact area of each raw material. Thus, since the reaction of each raw material can be promoted, the sulfide-based inorganic solid electrolyte material of the present embodiment can be obtained more efficiently.
[0078] Here, mechanochemical treatment refers to a method of vitrifying while applying mechanical energy such as shear force, collision force or centrifugal force to the mixed object. As a device for vitrification by mechanochemical treatment (hereinafter referred to as a vitrification device), a ball mill, a bead mill, a vibration mill, a turbine grinder, a mechanical fusion machine, a disc mill, a roller mill and other crushing / dispersing machines can be cited; a rotating / strike crushing device composed of a mechanism composed of a combination of rotation (shear stress) and impact (compression stress) represented by a rock drill, a vibration drill, an impact driver, etc.; a high-pressure grinding roller, etc. Among them, from the viewpoint of being able to efficiently generate very high impact energy, a ball mill and a bead mill are preferred, and a ball mill is particularly preferred. In addition, from the viewpoint of excellent continuous productivity, a roller mill is preferred; a rotating / strike crushing device composed of a mechanism composed of a combination of rotation (shear stress) and impact (compression stress) represented by a rock drill, a vibration drill, an impact driver, etc.; a high-pressure grinding roller; a roller-type vertical mill, a ball-type vertical mill and other vertical mills, etc.
[0079] In order to obtain the sulfide-based inorganic solid electrolyte material of the present embodiment, step (B) is preferably performed under an environment in which the presence and inflow of water and oxygen are suppressed to a higher level than before. Thus, the contact of the raw material composition with water and oxygen can be suppressed to a higher level than before.
[0080] Here, an environment in which the amount of water and oxygen present and the inflow thereof are suppressed to a higher level than before can be formed by, for example, the following method.
[0081] First, a mixing container and a sealed container for a vitrification device are placed in a glove box, and then the glove box is repeatedly (preferably 3 times or more) injected with an inert gas and vacuum degassed, wherein the inert gas is a high-purity dry argon gas, dry nitrogen gas, etc. obtained by a gas purification device. Here, in the glove box after the above operation, an inert gas such as a high-purity dry argon gas, dry nitrogen gas, etc. is circulated by a gas purification device to adjust the oxygen concentration and the water concentration to preferably 1.0 ppm or less, more preferably 0.8 ppm or less, and further preferably 0.6 ppm or less, respectively.
[0082] Next, lithium sulfide and phosphorus sulfide are added to the mixing container in the glove box, and then, a raw material composition is prepared by mixing (referring to step (A)). Here, lithium sulfide and phosphorus sulfide are added to the mixing container in the glove box according to the following steps. First, with the door inside the main body of the glove box closed, lithium sulfide and phosphorus sulfide are added to the side box of the glove box. Next, the side box is injected with an inert gas such as high-purity dry argon or dry nitrogen introduced from the glove box multiple times (preferably 3 times or more) and vacuum degassed, then, the door inside the main body of the glove box is opened, lithium sulfide and phosphorus sulfide are placed in the mixing container inside the main body of the glove box, and the mixing container is sealed.
[0083] Next, after lithium sulfide and phosphorus sulfide are mixed, the obtained raw material composition is taken out from the mixing container, transferred to a container for a vitrification device, and sealed.
[0084] By performing such an operation, the amount of water and oxygen present in the sealed container containing the raw material composition can be suppressed to a higher level than before. As a result, in step (B), an environment in which the amount of water and oxygen present can be suppressed to a higher level than before can be formed.
[0085] Then, take out the airtight container in which the raw inorganic composition is placed from the glove box. Next, a closed container is set in a vitrification device configured in an environment full of dry gases such as dry argon, dry nitrogen, dry air (for example, in a box full of dry argon, dry nitrogen, dry air, etc.), and vitrification is performed. Here, preferably, during the vitrification, a prescribed amount of dry gas is continuously introduced into an environment full of dry gas. By making such an improvement, in step (B), an environment in which the inflow of moisture and oxygen is suppressed at a higher level than before can be formed.
[0086] In addition, from the viewpoint of suppressing the inflow of moisture and oxygen into the sealed container at a high level and achieving higher airtightness, it is preferred to use a seal with excellent sealing properties such as an O-ring or a ferrule seal on the lid of the sealed container.
[0087] The mixing conditions such as the rotation speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the raw inorganic composition when the raw inorganic composition is mechanically treated can be appropriately determined according to the type and treatment amount of the raw inorganic composition. Generally, the faster the rotation speed, the faster the glass formation rate, and the longer the treatment time, the higher the glass conversion rate.
[0088] Generally, when performing X-ray diffraction analysis using CuKα rays as a radiation source, if the diffraction peak derived from the raw material disappears or decreases, it can be determined that the raw inorganic composition is vitrified and the desired sulfide-based inorganic solid electrolyte material can be obtained.
[0089] Here, in step (B), it is preferred that the vitrification treatment is performed until the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material by an AC impedance method under the measurement conditions of 27.0° C., an applied voltage of 10 mV, and a measurement frequency range of 0.1 Hz to 7 MHz becomes preferably 1.0×10 -4 S cm -1 More preferably 2.0×10 -4 S cm -1 More preferably, 3.0×10 -4 S cm -1 Above, particularly preferably 4.0×10 -4 S cm -1 As described above, a sulfide-based inorganic solid electrolyte material having even better lithium ion conductivity can be obtained.
[0090] (Adjust D 90 / Dm value process (C)
[0091] Then, the obtained sulfide-based inorganic solid electrolyte material is subjected to a classification process to obtain D 90 The / Dm value is adjusted to be within the range of 1.6 to 8.0.
[0092] For example, by classifying the obtained sulfide-based inorganic solid electrolyte material to adjust the particle size, a sulfide-based inorganic solid electrolyte material having a desired D can be obtained. 90 / Dm sulfide-based inorganic solid electrolyte material. The classification method is not particularly limited, and for example, at least one classification method selected from sieving and air flow classification can be used.
[0093] In addition, the sulfide-based inorganic solid electrolyte material can be further pulverized to further 90 The pulverization method is not particularly limited, and a known pulverization method such as a mixer, a jet mill, a mortar, a rotary mill, or a coffee grinder can be used.
[0094] These pulverization and classification are preferably performed under an inert gas atmosphere or a vacuum atmosphere from the viewpoint of preventing contact with moisture in the air.
[0095] (Step (D) of crystallizing at least a portion of the sulfide-based inorganic solid electrolyte material)
[0096] In the method for producing the sulfide-based inorganic solid electrolyte material of the present embodiment, a step of crystallizing at least a portion of the sulfide-based inorganic solid electrolyte material may be performed as needed. In step (D), the obtained glass-state sulfide-based inorganic solid electrolyte material is heated to crystallize at least a portion of the sulfide-based inorganic solid electrolyte material, thereby generating a sulfide-based inorganic solid electrolyte material in a glass ceramic state (also referred to as crystallized glass). In this way, a sulfide-based inorganic solid electrolyte material having further excellent lithium ion conductivity can be obtained.
[0097] That is, from the viewpoint of excellent lithium ion conductivity, the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably in a glass ceramic state (crystallized glass state).
[0098] The temperature at which the glassy sulfide-based inorganic solid electrolyte material is heated is preferably in the range of 220° C. to 500° C., and more preferably in the range of 250° C. to 350° C.
[0099] As long as the time for heating the glassy sulfide inorganic solid electrolyte material is the time for obtaining the desired glass ceramic sulfide inorganic solid electrolyte material, there is no particular limitation, for example, it is within the range of 0.5 hours to 24 hours, preferably 1 hour to 3 hours. There is no particular limitation on the heating method, for example, a method using a sintering furnace can be cited. It should be noted that in order to make the characteristics of the sulfide inorganic solid electrolyte material of the present embodiment most suitable, the temperature, time and other conditions during such heating can be appropriately adjusted.
[0100] In addition, it is preferable that the heating of the glassy sulfide-based inorganic solid electrolyte material be performed, for example, in an inert gas atmosphere, thereby preventing the sulfide-based inorganic solid electrolyte material from being degraded (for example, oxidized).
[0101] As the inert gas when heating the glassy sulfide-based inorganic solid electrolyte material, for example, argon, helium, nitrogen, etc. can be cited. In order to prevent impurities from being mixed into the product, the higher the purity of these inert gases, the better. In addition, in order to avoid contact with moisture, the dew point is preferably below -70°C, and particularly preferably below -80°C. As a method for introducing the inert gas into the mixed system, there is no particular limitation as long as the mixed system is filled with an inert gas environment. Examples include a method of purging the inert gas and a method of continuously introducing a specified amount of inert gas.
[0102] In order to obtain the sulfide-based inorganic solid electrolyte material of the present embodiment, it is important to appropriately adjust the above-mentioned steps. However, the method for producing the sulfide-based inorganic solid electrolyte material of the present embodiment is not limited to the above-mentioned method, and the sulfide-based inorganic solid electrolyte material of the present embodiment can be obtained by appropriately adjusting various conditions.
[0103] [Solid Electrolyte]
[0104] Next, the solid electrolyte of the present embodiment will be described. The solid electrolyte of the present embodiment includes the sulfide-based inorganic solid electrolyte material of the present embodiment.
[0105] Moreover, the solid electrolyte of the present embodiment is not particularly limited, and as a component other than the sulfide-based inorganic solid electrolyte material of the present embodiment, for example, a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above may be included within a range that does not impair the purpose of the present invention.
[0106] The solid electrolyte of the present embodiment may also include a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above. As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment, there is no particular limitation as long as it has ion conductivity and insulation, and materials commonly used in lithium-ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials that are different from the sulfide-based inorganic solid electrolyte material of the present embodiment can be cited; organic solid electrolyte materials such as polymer electrolytes.
[0107] As sulfide-based inorganic solid electrolyte materials different from the sulfide-based inorganic solid electrolyte materials of the present embodiment described above, for example, there can be cited Li2S-P2S5 materials, Li2S-SiS2 materials, Li2S-GeS2 materials, Li2S-Al2S3 materials, Li2S-SiS2-Li3PO4 materials, Li2S-P2S5-GeS2 materials, Li2S-Li2O-P2S5-SiS2 materials, Li2S-GeS2-P2S5-SiS2 materials, Li2S-SnS2-P2S5-SiS2 materials, Li2S-P2S5-Li3N materials, and Li2S 2+X -P4S3 material, Li2S-P2S5-P4S3 material, etc. These materials may be used alone or in combination of two or more.
[0108] Among them, Li2S-P2S5 materials are preferred from the viewpoint of excellent lithium ion conductivity and stability in a wide voltage range without causing decomposition, etc. Here, for example, Li2S-P2S5 materials refer to inorganic materials obtained by chemically reacting an inorganic composition containing at least Li2S (lithium sulfide) and P2S5 with each other through mechanical treatment.
[0109] Here, in the present embodiment, lithium sulfide also includes lithium polysulfide.
[0110] Examples of the oxide-based inorganic solid electrolyte material include NASICON-type (La 0.5+x Li 0.5-3x )TiO3 and other perovskite types, Li2O-P2O5 materials, Li2O-P2O5-Li3N materials, etc.
[0111] As other lithium-based inorganic solid electrolyte materials, for example, LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x N x (x is 0<x≤1), LiN, LiI, LISICON, etc.
[0112] Furthermore, glass ceramics obtained by precipitating crystals of these inorganic solid electrolytes can also be used as an inorganic solid electrolyte material.
[0113] As the organic solid electrolyte material, for example, a polymer electrolyte such as a dry polymer electrolyte or a gel electrolyte can be used.
[0114] As the polymer electrolyte, an electrolyte generally used for lithium ion batteries can be used.
[0115] [Solid electrolyte membrane]
[0116] Next, the solid electrolyte membrane of the present embodiment will be described.
[0117] The solid electrolyte membrane of the present embodiment includes a solid electrolyte as a main component, and the solid electrolyte contains the sulfide-based inorganic solid electrolyte material of the present embodiment described above.
[0118] The solid electrolyte membrane of the present embodiment is used to constitute a solid electrolyte layer of an all-solid-state lithium-ion battery, for example.
[0119] As an example of an all-solid-state lithium-ion battery to which the solid electrolyte membrane of the present embodiment is applied, there can be mentioned a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are sequentially stacked. In this case, the solid electrolyte layer is composed of a solid electrolyte membrane.
[0120] The average thickness of the solid electrolyte membrane of the present embodiment is preferably 5 μm or more and 500 μm or less, more preferably 10 μm or more and 200 μm or less, and further preferably 20 μm or more and 100 μm or less. When the average thickness of the solid electrolyte membrane is above the lower limit, the loss of solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed. In addition, when the average thickness of the solid electrolyte membrane is below the upper limit, the impedance of the solid electrolyte membrane can be further reduced. As a result, the battery characteristics of the obtained all-solid-state lithium-ion battery can be further improved.
[0121] The solid electrolyte membrane of the present embodiment is preferably a pressurized body of a particulate solid electrolyte comprising the sulfide-based inorganic solid electrolyte material of the present embodiment. That is, it is preferred that the particulate solid electrolyte is pressurized to form a solid electrolyte membrane having a predetermined strength due to the anchoring effect between the solid electrolyte materials.
[0122] By forming a press-molded body, the solid electrolytes are bonded to each other, and the strength of the obtained solid electrolyte membrane is further improved. As a result, the loss of solid electrolytes and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed.
[0123] When the solid electrolyte membrane as a whole is set to 100% by mass, the content of the sulfide-based inorganic solid electrolyte material of the present embodiment in the solid electrolyte membrane of the present embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more. Thus, the contact between the solid electrolytes is improved, and the interfacial contact resistance of the solid electrolyte membrane can be reduced. As a result, the lithium ion conductivity of the solid electrolyte membrane can be further improved. Moreover, by using such a solid electrolyte membrane with excellent lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium ion battery can be further improved.
[0124] The upper limit of the content of the sulfide-based inorganic solid electrolyte material of the present embodiment in the solid electrolyte membrane of the present embodiment is not particularly limited, but is, for example, 100% by mass or less.
[0125] The planar shape of the solid electrolyte membrane is not particularly limited and can be appropriately selected according to the shapes of the electrodes and the current collector, and can be, for example, a rectangular shape.
[0126] In addition, the solid electrolyte membrane of the present embodiment may contain a binder resin, and when the solid electrolyte membrane as a whole is set to 100 mass%, the content of the binder resin is preferably less than 0.5 mass%, more preferably 0.1 mass% or less, further preferably 0.05 mass% or less, and further preferably 0.01 mass% or less. In addition, it is further preferred that the solid electrolyte membrane of the present embodiment does not substantially contain a binder resin, and most preferably does not contain a binder resin.
[0127] Thus, the contact between solid electrolytes can be improved, and the interface contact resistance of the solid electrolyte membrane can be reduced. As a result, the lithium ion conductivity of the solid electrolyte membrane can be further improved. Moreover, by using such a solid electrolyte membrane with excellent lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium ion battery can be improved.
[0128] It should be noted that “substantially free of binder resin” means that it may be contained to the extent that the effect of the present embodiment is not impaired. In addition, when an adhesive resin layer is provided between the solid electrolyte layer and the positive electrode or the negative electrode, the adhesive resin from the adhesive resin layer present near the interface between the solid electrolyte layer and the adhesive resin layer is excluded from the “binder resin in the solid electrolyte membrane”.
[0129] The binder resin is a binder generally used in lithium ion batteries for bonding inorganic solid electrolyte materials, and examples thereof include polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, and polyimide.
[0130] For example, the solid electrolyte membrane of the present embodiment can be obtained by depositing a particulate solid electrolyte in a film shape on the cavity surface of a mold or on the surface of a substrate and then pressurizing the solid electrolyte deposited in a film shape.
[0131] There is no particular limitation on the method of pressurizing the above-mentioned solid electrolyte. For example, when the particulate solid electrolyte is deposited on the cavity surface of the mold, pressurization based on the mold and the press die can be used; when the particulate solid electrolyte is deposited on the surface of the substrate, pressurization based on the mold and the press die, roller pressing, flat plate pressing, etc. can be used.
[0132] The pressure at which the solid electrolyte is pressurized is, for example, 10 MPa to 500 MPa.
[0133] In addition, as required, the inorganic solid electrolyte deposited in a film form may be pressurized and heated at the same time. As long as the heating and pressurization are performed, the fusion and bonding between the solid electrolytes will be caused, and the strength of the obtained solid electrolyte membrane will be further improved. As a result, the loss of solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed.
[0134] The temperature for heating the solid electrolyte is, for example, 40° C. or higher and 500° C. or lower.
[0135] [Lithium-ion battery]
[0136] Figure 1 1 is a cross-sectional view showing an example of the structure of a lithium ion battery 100 according to an embodiment of the present invention.
[0137] The lithium ion battery 100 of the present embodiment has, for example, a positive electrode 110 including a positive electrode active material layer 101, an electrolyte layer 120, and a negative electrode 130 including a negative electrode active material layer 103. Moreover, at least one of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contains the sulfide-based inorganic solid electrolyte material of the present embodiment. In addition, it is preferred that the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 all contain the sulfide-based inorganic solid electrolyte material of the present embodiment. It should be noted that, in the present embodiment, unless otherwise specified, the layer containing the positive electrode active material is referred to as the positive electrode active material layer 101. As required, the positive electrode 110 may include a collector 105 in addition to the positive electrode active material layer 101, or may not include the collector 105. In addition, in the present embodiment, unless otherwise specified, the layer containing the negative electrode active material is referred to as the negative electrode active material layer 103. The negative electrode 130 may include a current collector 105 in addition to the negative electrode active material layer 103 , or may not include the current collector 105 , as necessary.
[0138] The shape of the lithium ion battery 100 of the present embodiment is not particularly limited, and may be any other shape such as a cylinder, a coin, a rectangle, or a film.
[0139] The lithium ion battery 100 of this embodiment is manufactured by a commonly known method, for example, by stacking the positive electrode 110, the electrolyte layer 120, and the negative electrode 130 to form a cylindrical, coin-shaped, rectangular, film-shaped, or other arbitrary shape, and sealing a non-aqueous electrolyte as needed.
[0140] (positive electrode)
[0141] There is no particular limitation on the positive electrode 110, and a positive electrode commonly used in lithium ion batteries can be used. There is no particular limitation on the positive electrode 110, and it can be manufactured according to a generally known method. For example, it can be obtained by forming a positive electrode active material layer 101 containing a positive electrode active material on the surface of a current collector 105 such as aluminum foil.
[0142] The thickness and density of the positive electrode active material layer 101 are appropriately determined according to the intended use of the battery, and therefore are not particularly limited and can be set according to generally known information.
[0143] The positive electrode active material layer 101 contains a positive electrode active material.
[0144] There are no particular limitations on the positive electrode active material, and commonly known positive electrode active materials can be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2), olivine-type lithium phosphorus oxide (LiFePO4) and other composite oxides; conductive polymers such as polyaniline and polypyrrole; sulfide-based positive electrode active materials such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, Li-Mo-S compounds, Li-Ti-S compounds, Li-VS compounds, and Li-Fe-S compounds; materials with sulfur as active material such as sulfur-impregnated acetylene black, sulfur-impregnated porous carbon, and mixed powders of sulfur and carbon. These positive electrode active materials can be used alone or in combination of two or more.
[0145] Among them, from the viewpoint of having a higher discharge capacity density and better cycle characteristics, a sulfide-based positive electrode active material is preferred, and one or more selected from a Li-Mo-S compound, a Li-Ti-S compound, and a Li-VS compound is more preferred.
[0146] Here, the Li—Mo—S compound contains Li, Mo, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing molybdenum sulfide and lithium sulfide as raw materials with each other through mechanical treatment.
[0147] The Li—Ti—S compound contains Li, Ti, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing titanium sulfide and lithium sulfide as raw materials by mechanical treatment.
[0148] The Li—VS compound contains Li, V, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing vanadium sulfide and lithium sulfide as raw materials with each other through mechanical treatment.
[0149] The positive electrode active material layer 101 is not particularly limited, and may include, as components other than the positive electrode active material, at least one material selected from a binder resin, a thickener, a conductive additive, a solid electrolyte material, etc. Each material will be described below.
[0150] The positive electrode active material layer 101 may contain a binder resin having a function of binding the positive electrode active materials to each other and binding the positive electrode active material to the current collector 105 .
[0151] The binder resin of the present embodiment is not particularly limited as long as it is a common binder resin that can be used for lithium ion batteries, and examples thereof include polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyimide, etc. These binders may be used alone or in combination of two or more.
[0152] From the viewpoint of ensuring the fluidity of the slurry suitable for coating, the positive electrode active material layer 101 may also include a thickener. As a thickener, as long as it is a common thickener that can be used for lithium ion batteries, there is no particular limitation, for example, cellulose polymers such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose and their ammonium salts and alkali metal salts, polycarboxylic acids, polyethylene oxide, polyvinyl pyrrolidone, polyacrylates, polyvinyl alcohol and other water-soluble polymers, etc. can be cited. These thickeners can be used alone or in combination of two or more.
[0153] The positive electrode active material layer 101 may contain a conductive aid from the viewpoint of improving the conductivity of the positive electrode 110. The conductive aid is not particularly limited as long as it is a common conductive aid that can be used for lithium ion batteries, and examples thereof include carbon black such as acetylene black and Ketjen black, and carbon materials such as vapor-grown carbon fibers.
[0154] The positive electrode of the present embodiment may contain a solid electrolyte comprising the sulfide-based inorganic solid electrolyte material of the present embodiment described above, or may contain a solid electrolyte comprising a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment. As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment, there is no particular limitation as long as it has ion conductivity and insulation, and solid electrolyte materials commonly used in lithium-ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials; organic solid electrolyte materials such as polymer electrolytes. More specifically, the inorganic solid electrolyte materials cited in the description of the solid electrolyte of the present embodiment can be used.
[0155] Since the mixing ratio of each material in the positive electrode active material layer 101 is appropriately determined according to the use of the battery, etc., it is not particularly limited and can be set according to generally known information.
[0156] (negative electrode)
[0157] There is no particular limitation on the negative electrode 130, and a negative electrode commonly used in lithium-ion batteries can be used. There is no particular limitation on the negative electrode 130, and it can be manufactured according to a generally known method. For example, it can be obtained by forming a negative electrode active material layer 103 containing a negative electrode active material on the surface of a current collector 105 such as copper.
[0158] The thickness and density of the negative electrode active material layer 103 are appropriately determined according to the intended use of the battery, and therefore are not particularly limited and can be set according to generally known information.
[0159] The negative electrode active material layer 103 contains a negative electrode active material.
[0160] The negative electrode active material is not particularly limited as long as it is a common negative electrode active material that can be used for the negative electrode of a lithium ion battery. For example, carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon can be cited; metal materials based on lithium, lithium alloys, tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacene, polyacetylene, and polypyrrole; lithium titanium composite oxides (such as Li4Ti5O 12 ) etc. These negative electrode active materials may be used alone or in combination of two or more.
[0161] The negative electrode active material layer 103 is not particularly limited, and as components other than the negative electrode active material, for example, it may also contain one or more materials selected from a binder resin, a thickener, a conductive aid, a solid electrolyte material, etc. These materials are not particularly limited, and for example, the same materials as those used in the positive electrode 110 can be cited.
[0162] Since the mixing ratio of each material in the negative electrode active material layer 103 is appropriately determined according to the use of the battery, etc., it is not particularly limited and can be set according to generally known information.
[0163] (Electrolyte layer)
[0164] Next, the electrolyte layer 120 will be described. The electrolyte layer 120 is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103 .
[0165] Examples of the electrolyte layer 120 include a layer in which a separator is impregnated with a non-aqueous electrolyte solution and a solid electrolyte layer containing a solid electrolyte.
[0166] The separator of this embodiment is not particularly limited as long as it electrically insulates the positive electrode 110 and the negative electrode 130 and has a function of allowing lithium ions to pass therethrough. For example, a porous film can be used.
[0167] As the porous film, a microporous polymer film is preferably used, and examples of the material include polyolefin, polyimide, polyvinylidene fluoride, polyester, etc. In particular, a porous polyolefin film is preferred, and specific examples include a porous polyethylene film, a porous polypropylene film, and the like.
[0168] The non-aqueous electrolyte solution is an electrolyte solution in which an electrolyte is dissolved in a solvent.
[0169] As the electrolyte, any known lithium salt can be used, and it can be selected according to the type of active material. For example, LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, lower fatty acid carboxylic acid lithium, etc.
[0170] The solvent for dissolving the above-mentioned electrolyte is not particularly limited as long as it is a solvent commonly used as a liquid for dissolving the electrolyte, and examples thereof include carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), and vinylene carbonate (VC); lactones such as γ-butyrolactone and γ-valerolactone; ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; and sulfoxides such as dimethyl sulfoxide. 1,3-dioxolane, 4-methyl-1,3-dioxolane and other oxolanes; acetonitrile, nitromethane, formamide, dimethylformamide and other nitrogen-containing compounds; methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate and other organic acid esters; triesters of phosphate, diethylene glycol dimethyl ether (diglyme); triethylene glycol dimethyl ether (triglyme); sulfolanes such as sulfolane and methyl sulfolane; oxazolidinones such as 3-methyl-2-oxazolidinone; sultones such as 1,3-propane sultone, 1,4-butane sultone and naphthalene sultone, etc. These materials may be used alone or in combination of two or more.
[0171] The solid electrolyte layer of this embodiment is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103, and is a layer formed of a solid electrolyte containing a solid electrolyte material. There are no particular limitations as long as the solid electrolyte contained in the solid electrolyte layer has lithium ion conductivity. In this embodiment, a solid electrolyte containing a sulfide-based inorganic solid electrolyte material of this embodiment is preferred.
[0172] As long as the content of the solid electrolyte in the solid electrolyte layer of the present embodiment is a ratio that can obtain the desired insulation, there is no particular limitation, for example, it is in the range of 10 volume % or more and 100 volume % or less, and preferably in the range of 50 volume % or more and 100 volume % or less. In particular, in the present embodiment, it is preferred that the solid electrolyte layer is composed only of a solid electrolyte containing the sulfide-based inorganic solid electrolyte material of the present embodiment.
[0173] In addition, the solid electrolyte layer of the present embodiment may also contain a binder resin. By containing a binder resin, a flexible solid electrolyte layer can be obtained. As a binder resin, for example, fluorine-containing binders such as polytetrafluoroethylene and polyvinylidene fluoride can be cited. The thickness of the solid electrolyte layer is, for example, in the range of 0.1 μm or more and 1000 μm or less, preferably in the range of 0.1 μm or more and 300 μm or less.
[0174] As mentioned above, although embodiment of this invention was described, these are an example of this invention, and various structures other than the above-mentioned can also be adopted.
[0175] It should be noted that the present invention is not limited to the above-described embodiments, and modifications, improvements, etc. within the scope that can achieve the object of the present invention are also included in the present invention.
[0176] Example
[0177] Hereinafter, the present invention will be described by way of Examples and Comparative Examples, but the present invention is not limited thereto.
[0178] [1] Measurement method
[0179] First, the measurement methods in the following Examples and Comparative Examples are described.
[0180] (1) Particle size distribution
[0181] The SEM image of the obtained sulfide-based inorganic solid electrolyte material was analyzed by using the image processing software disclosed by the National Institutes of Health (National Institutes of Health free software, ImageJ, v1.52a), thereby obtaining the number-based particle size distribution, and the most frequent particle size Dm and the particle size Dm with a cumulative frequency of 90% were calculated based on this. 90 .
[0182] As a step, first, a carbon tape is attached to the sample stage of the SEM, so that a trace of particles of the sulfide-based inorganic solid electrolyte material is attached to the carbon tape in a thin and widely scattered state. Then, the SEM image of the sulfide-based inorganic solid electrolyte material is taken. The obtained SEM image is read into ImageJ. Correction is implemented according to the scale displayed in the SEM image. Then, the image is converted into a black and white binary. At this time, a threshold is set to make the outline of the particle clear. When there are overlapping particles in the obtained black and white image, as an image processing based on ImageJ, the overlapping separation between the particles is performed by the watershed method. Moreover, as an image analysis based on ImageJ, particle analysis is performed to obtain the measurement result of the particle size based on the Feret diameter (Feretdiameter). Finally, the measurement result of the obtained particle size is read into the spreadsheet calculation software EXCEL (registered trademark) of Microsoft Corporation, so that the particle size is arranged in order from small to large, and the number is counted, thereby obtaining the particle size distribution.
[0183] In each of the Examples and Comparative Examples, the particle diameters of 3,000 or more particles were measured to obtain a number-based particle size distribution.
[0184] (2) Determination of composition ratio of sulfide-based inorganic solid electrolyte material
[0185] The mass % of Li, P and S in the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples were determined by ICP emission spectrometry using an ICP emission spectrometer (SPS3000, manufactured by Seiko Instruments Inc.), and the molar ratio of each element was calculated based on the mass %.
[0186] (3) Determination of lithium ion conductivity
[0187] The lithium ion conductivity of the sulfide-based inorganic solid electrolyte materials obtained in Examples and Comparative Examples was measured by an alternating current impedance method.
[0188] Lithium ion conductivity was measured using a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Inc. The sample size was 9.5 mm in diameter and 1.2 to 2.0 mm in thickness, and the measurement conditions were an applied voltage of 10 mV, a measurement temperature of 27.0°C, a measurement frequency range of 0.1 Hz to 7 MHz, and the electrode was a Li foil.
[0189] Here, as a sample for measuring lithium ion conductivity, a plate-like sulfide-based inorganic solid electrolyte material having a diameter of 9.5 mm and a thickness of 1.2 to 2.0 mm was used. The plate-like sulfide-based inorganic solid electrolyte material was obtained by pressurizing 150 mg of the powdered sulfide-based inorganic solid electrolyte material obtained in the examples and comparative examples under the conditions of 270 MPa for 10 minutes using a pressurizing device.
[0190] (4) Determination of the maximum value of the oxidation decomposition current
[0191] Using a pressurizing device, 120 to 150 mg of the powdered sulfide-based inorganic solid electrolyte material obtained in the examples and comparative examples was pressurized at 270 MPa for 10 minutes to obtain a plate-like sulfide-based inorganic solid electrolyte material (particles) having a diameter of 9.5 mm and a thickness of 1.3 mm. Subsequently, a Li foil as a reference electrode / counter electrode was press-bonded to one surface of the obtained particles at 18 MPa for 10 minutes, and a SUS314 foil as a working electrode was closely bonded to the other surface.
[0192] Next, using a potentiostat / galvanostat SP-300 manufactured by BioLogics, the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material was determined at a temperature of 25°C, a scanning voltage range of 0 to 5 V, and a voltage scanning rate of 5 mV / sec, and evaluated according to the following criteria.
[0193] ◎: 0.03μA or less;
[0194] 0: greater than 0.03μA and less than 0.50μA;
[0195] ×: greater than 0.50 μA.
[0196] [2] Manufacture of sulfide-based inorganic solid electrolyte materials
[0197] <Example 1>
[0198] The sulfide-based inorganic solid electrolyte material was prepared according to the following steps.
[0199] As raw materials, Li2S (produced by Furukawa Machinery & Metal Co., Ltd., purity 99.9%), P2S5 (produced by Kanto Chemical Co., Ltd.), and Li3N (produced by Furukawa Machinery & Metal Co., Ltd.) were used respectively.
[0200] Next, in an argon glove box, Li2S powder, P2S5 powder, and Li3N powder (Li2S:P2S5:Li3N=27:9:2 (molar ratio)) were precisely weighed and mixed in an agate mortar for 10 minutes.
[0201] Next, weigh 2 g of the mixed powder and add 18 The zirconia balls were put into a zirconia container (content 45 mL), and pulverized and mixed (mechanical chemical treatment) for 12 hours using a planetary ball mill (rotation 800 rpm, revolution 400 rpm).
[0202] Next, the powder adhering to the inner wall of the container and the balls was scraped off, and the powder and the balls were put into the same container again, and the mixture was pulverized and mixed using a planetary ball mill (rotation 800 rpm, revolution 400 rpm) for the same time as before, to obtain a glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).
[0203] Next, the glass-state sulfide-based inorganic solid electrolyte material was annealed in argon at 300° C. for 7 hours to obtain a glass-ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).
[0204] Next, the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was classified by passing through a sieve having an opening of 20 μm.
[0205] The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were subjected to various evaluations. The obtained results are shown in Table 1.
[0206] <Example 2>
[0207] Weigh 400 g of the sulfide-based inorganic solid electrolyte material obtained in Example 1 and 6200 g of zirconia balls were placed in an alumina container (content 5 L), and the mixture was pulverized for 120 hours while being shaken in a ball mill (rotation speed 100 rpm) to obtain a glassy sulfide-based inorganic solid electrolyte material. The glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300 ° C for 7 hours to obtain a glass-ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were evaluated. The obtained results are shown in Table 1.
[0208] <Example 3>
[0209] The sulfide-based inorganic solid electrolyte material obtained in Example 2 was classified by passing through a sieve having an opening of 20 μm.
[0210] The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were subjected to various evaluations. The obtained results are shown in Table 1.
[0211] <Example 4>
[0212] Weigh 400 g of the sulfide-based inorganic solid electrolyte material obtained in Example 1 and 6200 g of zirconia balls were placed in an alumina container (content 5 L), and the mixture was pulverized for 24 hours while being shaken in a ball mill (rotation speed 100 rpm) to obtain a glassy sulfide-based inorganic solid electrolyte material. The glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300 ° C for 7 hours to obtain a sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).
[0213] The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were subjected to various evaluations. The obtained results are shown in Table 1.
[0214] <Example 5>
[0215] The sulfide-based inorganic solid electrolyte material was prepared according to the following steps.
[0216] As raw materials, Li2S (produced by Furukawa Metals Co., Ltd., purity 99.9%), P2S5 (produced by Kanto Chemical Co., Ltd.), and Li3N (produced by Furukawa Metals Co., Ltd.) were used.
[0217] Next, in an argon glove box, Li2S powder, P2S5 powder, and Li3N powder (Li2S:P2S5:Li3N=27:9:2 (molar ratio)) were precisely weighed and mixed in an agate mortar for 10 minutes.
[0218] Next, weigh 500 g of the mixed powder and Zirconia ball 7500g and 700 g of zirconia balls were put into an alumina container (internal volume 5.0 L), and the mixture was pulverized and mixed using a ball mill (rotation speed 100 rpm) for 48 hours (mechanical chemical treatment).
[0219] Next, after scraping off the crushed and mixed powder attached to the inner wall of the container and the balls, the powder and the balls are put into the same container again, and crushed and mixed using a ball mill (rotation speed 100 rpm) for the same time as before. The operation from scraping to crushing is repeated until a total of 700 hours is reached to obtain a glassy sulfide-based inorganic solid electrolyte material.
[0220] Next, weigh 300g of it and 6200 g of zirconia balls were put into an alumina container (content 5 L), and the mixture was crushed for 50 hours while being shaken by a ball mill (rotation speed 100 rpm) to obtain a fine glassy sulfide-based inorganic solid electrolyte material.
[0221] Next, the glass-state sulfide-based inorganic solid electrolyte material was annealed in argon at 300° C. for 7 hours to obtain a glass-ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).
[0222] Next, the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was classified by passing through a sieve having an opening of 20 μm.
[0223] The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were subjected to various evaluations.
[0224] <Example 6>
[0225] In Example 5, 300 g of a glassy sulfide-based inorganic solid electrolyte material was mixed with Zirconia ball 1200g, Zirconia ball 6200g, 1200 g of zirconia balls were placed in an alumina container (content 5 L) and pulverized for 50 hours while being shaken in a ball mill (rotation speed 100 rpm). A sulfide-based inorganic solid electrolyte material in a glass ceramic state was obtained by the same procedure except that 6200 g of zirconia balls were crushed.
[0226] The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were subjected to various evaluations.
[0227] <Comparative Example 1>
[0228] Weigh 400 g of the sulfide-based inorganic solid electrolyte material obtained in Example 1 and 6200 g of zirconia balls were placed in an alumina container (content 5 L), and the mixture was pulverized for 24 hours while being shaken in a ball mill (rotation speed 100 rpm) to obtain a glassy sulfide-based inorganic solid electrolyte material. The glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300 ° C for 7 hours to obtain a sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).
[0229] The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were subjected to various evaluations. The obtained results are shown in Table 1.
[0230] <Comparative Example 2>
[0231] In the same manner as in Example 1, the glass-ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ). No sieving was then performed.
[0232] The obtained sulfide-based inorganic solid electrolyte materials in a glass ceramic state were subjected to various evaluations. The obtained results are shown in Table 1.
[0233] Table 1
[0234]
[0235] The sulfide-based inorganic solid electrolyte materials of Examples 1 to 4 were excellent in lithium ion conductivity and electrochemical stability. In contrast, the sulfide-based inorganic solid electrolyte materials of Comparative Examples 1 and 2 were inferior in lithium ion conductivity.
[0236] Here, the number-based particle size distribution of the sulfide-based inorganic solid electrolyte materials obtained in Examples and Comparative Examples is shown in FIG. Figure 2 .
[0237] Table 2
[0238]
[0239] The sulfide-based inorganic solid electrolyte materials of Examples 5 and 6 are excellent in lithium ion conductivity and electrochemical stability.
[0240] Here, the number-based particle size distribution of the sulfide-based inorganic solid electrolyte materials obtained in Example 5 and Example 6 is shown in FIG. Figure 3 .
[0241] This application is based on and claims the benefit of priority of Japanese Patent Application No. 2020-073649 filed on April 16, 2020 and Japanese Patent Application No. 2020-168520 filed on October 5, 2020, the entire contents of which are incorporated herein.
[0242] Description of Reference Numerals
[0243] 100: Lithium-ion battery;
[0244] 101: positive electrode active material layer;
[0245] 103: negative electrode active material layer;
[0246] 105: current collector;
[0247] 110: positive electrode;
[0248] 120: electrolyte layer;
[0249] 130: Negative pole.
Claims
1. A sulfide-based inorganic solid electrolyte material having lithium ion conductivity, wherein: The sulfide-based inorganic solid electrolyte material is in the form of particles. In the number-based particle size distribution of the sulfide-based inorganic solid electrolyte material obtained from the observation image of the scanning electron microscope SEM, the mode particle size is denoted as Dm, and the particle size at which the cumulative frequency of the number-based particle size distribution is 90% is denoted as D 90 hour, D 90 / Dm value is 1.6 or more and 8.0 or less, The Dm, D 90 The unit is μm, The sulfide-based inorganic solid electrolyte material contains Li, P and S as constituent elements, In the sulfide-based inorganic solid electrolyte material, a molar ratio Li / P of the Li content to the P content is 1.0 to 5.0, and a molar ratio S / P of the S content to the P content is 2.0 to 6.
0.
2. The sulfide-based inorganic solid electrolyte material according to claim 1, wherein The mode particle size Dm is 10.0 μm or less.
3. The sulfide-based inorganic solid electrolyte material according to claim 1 or 2, wherein The sulfide-based inorganic solid electrolyte material is used in lithium-ion batteries.
4. A solid electrolyte, wherein: The invention comprises the sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 3.
5. A solid electrolyte membrane, wherein: Containing the solid electrolyte according to claim 4 as a main component.
6. The solid electrolyte membrane according to claim 5, wherein The solid electrolyte membrane is a press-molded body of the solid electrolyte in a particle form.
7. The solid electrolyte membrane according to claim 5 or 6, wherein: When the entire solid electrolyte membrane is taken as 100 mass %, the content of the binder resin in the solid electrolyte membrane is less than 0.5 mass %.
8. The solid electrolyte membrane according to claim 5 or 6, wherein: When the entire solid electrolyte membrane is taken as 100 mass %, the content of the sulfide-based inorganic solid electrolyte material in the solid electrolyte membrane is 50 mass % or more.
9. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 3.
10. A method for producing a sulfide-based inorganic solid electrolyte material, the method being for producing the sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 3, wherein: include: Step A, preparing a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and phosphorus sulfide; Step B, mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material, thereby causing the lithium sulfide and the phosphorus sulfide as raw materials to undergo a chemical reaction and simultaneously undergo vitrification, thereby obtaining a sulfide-based inorganic solid electrolyte material in a glass state; and Step C, by classifying the obtained sulfide-based inorganic solid electrolyte material, 90 The / Dm value is adjusted to be within the range of 1.6 to 8.
0.
11. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 10, wherein: The raw material composition of the sulfide-based inorganic solid electrolyte material further includes lithium nitride.
12. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 10 or 11, wherein: In the step C, the sulfide-based inorganic solid electrolyte material is classified using at least one classification method selected from sieving and air flow classification.
Citation Information
Patent Citations
Sulfide solid electrolytic material, battery, and method for manufacturing sulfide solid electrolytic material
JP2016027545A
Refrigeration cycle apparatus
JP2020073649A
Game machine
JP2020168520A
Carbon material, method for producing carbon material, and non-aqueous secondary battery using carbon material
CN107112536A
Lithium, phosphorus, sulfur, and iodine including electrolyte and catholyte compositions, electrolyte membranes for electrochemical devices, and annealing methods of making these electrolytes and catholytes
CN108604705A